Gerstmann syndrome in a young man: a case report - Iv. Dimitrov; S. Atanasova; A. Kaprelyan; B. Ivanov; V. Nestorova; K. Drenska; Zh. Chuperkova; Iv. Aleksandrov (Trakia Journal of Sciences)
Gerstmann syndrome is a classical cerebral syndrome in neurology, named after Joseph Gerstmann, a Jewish Austrian-born American neurologist. Patients present with a tetrad of cognitive symptoms, including agraphia, acalculia, finger agnosia and left-right disorientation. The syndrome is known to result from a lesion of the posterior portion of the dominant parietal lobe and is usually due to stroke or to developmental problems. We describe the case of a 35-year-old man whose illness debuted about 9 months before the initial presentation to the neurology clinic, with memory complaints, anxiety, verbal aggression, sleeping problems, as well as subjective word finding difficulty and depressed mood. The patient had 3 out of the 4 classic symptoms of Gerstmann syndrome, among other, mostly neuropsychiatric symptoms. Initially, structural lesions were sought for, but were not found on magnetic resonance imaging. Psychiatric conditions were discussed but not confirmed by the consulting psychiatrist. We are prone to accepting a non-organic reason for the condition of the patient, but follow-up of the clinical course and repeated assessments, including neuropsychological and psychiatric evaluations, structural and possibly functional neuroimaging will be required to verify and confirm this presumption.